Infants, Museums and Mediation: from the aesthetic dimension to relationships - Cristina Carvalho; Maria Emília Tagliari Santos (Universidade Federal do Rio Grande do Sul, 2019)
This article is part of the master's dissertation 'Babies in the Art Museum: Processes, Relations and Discoveries'. From the analysis of sessions of the program No Colo (On One's Arms), from the Instituto Tomie Ohtake, in São Paulo, we aimed to understand the inclusion of infants in education programs in art museums. Based on the investigation and analysis of the practices in question and dialoguing with the adopted theoretical framework - Vygotsky, Trevarthen, Vecchi - we observed that the contact with artifacts, collective experiences and proposals for sensory experimentation can be significant for infants' social, emotional and cognitive development and insertion in culture. The inclusion of this audience can provide new ways of being and thinking about exhibition spaces, contributing to its democratization and broadening of the mediation repertoire.